2010
DOI: 10.3233/ies-2010-0377
|View full text |Cite
|
Sign up to set email alerts
|

Differences in back extensor muscles fatigability for smoking and non-smoking athletes

Abstract: Background and objective: Empirical research on the influence of smoking on musculoskeletal health in athletes is sparse. The objective of this study was to compare back extensor muscles' strength (BEMS) before and after a fatigue induction protocol among smoking and non smoking male athletes. A pretest -posttest design was used to determine the difference in BEMS between smoking (N = 52) and non smoking (N = 52) athletes aged 18 and 30. A back and leg dynamometer was used to quantify BEMS while repetitive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Twelve studies examined the effects of smoking on physical and functional properties of skeletal muscle: 7 studies examined muscle strength, 2 studies examined muscle thickness, and 3 focused on maximal voluntary contraction. The findings of the 3 pretest/posttest, 2 prospective cohort, and 2 cross-sectional studies on muscle strength were that smoking was significantly associated with a reduction in back extensor muscle strength [ 202 , 208 ], grip strength [ 203 , 215 ], and knee muscle strength [ 207 ]. One prospective cohort study reported that parameters of body composition and muscle strength were increased in subjects who quit smoking compared to subjects who continued smoking [ 218 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies examined the effects of smoking on physical and functional properties of skeletal muscle: 7 studies examined muscle strength, 2 studies examined muscle thickness, and 3 focused on maximal voluntary contraction. The findings of the 3 pretest/posttest, 2 prospective cohort, and 2 cross-sectional studies on muscle strength were that smoking was significantly associated with a reduction in back extensor muscle strength [ 202 , 208 ], grip strength [ 203 , 215 ], and knee muscle strength [ 207 ]. One prospective cohort study reported that parameters of body composition and muscle strength were increased in subjects who quit smoking compared to subjects who continued smoking [ 218 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mattey et al, 2011 41 Smokers showed high scores of Bath AS Functional Index as compared to nonsmokers. Adedoyin et al, 2010 42 Athletes who smoke showed high rate of exertion and fatigue index as compared to nonsmoker athletes. Kim & Kim, 2012 43 Smokers are more dependent on internal oblique and transverse abdominis muscles as compared to nonsmokers.…”
Section: Romanos Et Al 2013 37mentioning
confidence: 99%
“…The highest reading out of the 3 was recorded. [15][16][17] Backward Overhead Medicine Ball Throw Test. This test was used to determine upper-body throwing power using a 3 kg medicine ball, which was thrown overhead as far as possible.…”
Section: Back Strength Testingmentioning
confidence: 99%